Densifikasi Produk Karbonisasi Pelepah Sawit Menjadi Briket Menggunakan Crude Gliserol Produk Samping Biodiesel Sebagai Filler - Arief Maulana Ilham; Zuchra Helwani; Warman Fatra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm frond has been utilized only for raw source of animal feed, compost and organic fertilizer in plantation area. Oil palm fronds has calorific value of 17.200 kJ/kg. Calorific value can be enhanced by carbonization followed by densification. By carbonization, the elements of smoke maker is able to be minimalized, so it will produce the green exhaust gases. Biomass densification aims to increase density and decrease handling issue such as storage and transportation. Calorific value of densification product can be enhanced more by adding filler like crude glycerol that has calorific value of 25.932,75 kJ/kg. This research aims to produce bricket using densification form palm fronds, to know the impact of particle size, filler composition and pressing pressure in product forming also to know the resulted calorific value and compressive strength of resulted product. Particle size used were 60, 80 dan 100 mesh. Filler composition used were 90 : 10, 80 : 20 dan 70 : 30. Pressing pressure used were 80, 90 dan 100 bar. Highest calorific value resulted was 27.359 kJ/kg at 100 mesh particle size, filler composition of 90:10 and pressing pressure of 100 bar. Highest compressive strength resulted was 37,2 Kg/cm2 at 60 mesh particle size, filler composition of 90:10 and pressing sressure of 100 bar. The most affecting factor to calorific value and compressive strength are filler composition and pressing pressureKeywords: Densification, Carbonization, Compressive Strength, Calorific Value, Oil Palm Fronds